Niobium Pentachloride Mediated Direct Bradsher-Type Reaction: A Rapid and Efficient Strategy to Synthesize Novel Substituted 9-Anthraldehydes - Baviera, Giovanni S.; Donate, Paulo M. (Synlett, 2023)
Dichloromethyl methyl ether in the presence of niobium pentachloride and activated triarylmethanes leads to an efficient, mild, and rapid one-pot synthesis of several 9-anthraldehyde derivatives via a direct Bradsher-type reaction. This practical methodology offers several advantages, such as a broad substrate scope, simple workup process, and excellent yields.
Keywords: anthracene; Bradsher reaction; anthraldehyde; niobium catalysis; triarylmethanes